GAGASAN ISLAM CINTA: SEBUAH TELAAH FILOSOFIS - Deden Ridwan (Ushuluna: Jurnal Ilmu Ushuluddin, 2020)
This article in fact gives an overview of Islam as love. Although never referred to as a sect or movement, Islam as love  belongs to the Sufis. Even it had been centuries, especially in the tasawuf or irfān tradition (sufismtheoretical-philosophical). Islam is built on three pillars: īmān (faith), islām (shari'a), and iḥsān (love). Frequently, we see the first two pillars so prequently used, while  people often forget that  akidah (faith) can be gained as a blessing when it is implemented jointly with the implementation of iḥsān (love). This element of “love” should be restored in religious life, as the third pillar of Islam. This is what we call “Islam mazhab cinta”. Islam that brings God’s mercy, which presents cordiality, not anger